Some aspects of the gradient-holomic algorithm in the theory of integration of nonlinear dynamic systems and the problems of computer algebra - Mitropolsky , Yu. O.; Prikarpatsky , A. K.; Fil В. M. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Some aspects are considered of a gradient holonomic algorithm in the theory of integrability of nonlinear dynamic systems. The gradient holonomic method yields recursion operators that explicitly contain a space variable and a time variable. An algorithm is presented that makes it possible to integrate by computer methods expressions which contain the derivatives of an unknown function.